2019
DOI: 10.1038/s41388-019-1102-1
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy impacts on the cellular response to CDK4/6 inhibition: distinct mechanisms of interaction and efficacy in models of pancreatic cancer

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a therapy recalcitrant disease characterized by the aberrations in multiple genes that drive pathogenesis and limit therapeutic response. While CDK4/6 represents a downstream target of both KRAS mutation and loss of the CDKN2A tumor suppressor in PDAC, clinical and preclinical studies indicate that pharmacological CDK4/6 inhibitors are only modestly effective. Since chemotherapy represents the established backbone of PDAC treatment we evaluated the interaction of CDK4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 45 publications
0
26
0
1
Order By: Relevance
“…CDK, which is one of the most critical molecules for several cell cycle transitions, has recently been considered a key target to treat ER-positive breast cancer. Indeed, the results of recent clinical trials indicate that combinations of cell cycle inhibitors and other drugs may be one of the most promising therapeutic approaches to breast cancer in the future [6,[34][35][36][37][38]. To this end, we cannot help but speculate that the G2M pathway score may have a utility to be used for patient selection and as a predictive biomarker for CDK inhibitors among patients with ER-positive breast cancer.…”
Section: Discussionmentioning
confidence: 89%
“…CDK, which is one of the most critical molecules for several cell cycle transitions, has recently been considered a key target to treat ER-positive breast cancer. Indeed, the results of recent clinical trials indicate that combinations of cell cycle inhibitors and other drugs may be one of the most promising therapeutic approaches to breast cancer in the future [6,[34][35][36][37][38]. To this end, we cannot help but speculate that the G2M pathway score may have a utility to be used for patient selection and as a predictive biomarker for CDK inhibitors among patients with ER-positive breast cancer.…”
Section: Discussionmentioning
confidence: 89%
“…Our group and others have reported that tumor immune microenvironment (TIME) is deeply involved in cancer progression in multiple settings [ 58 , 59 , 60 ]. Cell cycle activity was recently reported to correlate with increased anti-tumor immunity in multiple cancers [ 61 ], and CDK4/6 inhibition was reported to trigger anti-cancerous immunity [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…Despite the observed antagonism between CDK4/6 inhibitors and DNA-or mitotic-damaging agents, a few studies in the last few years suggest that CDK4/6 inhibitors may actually cooperate with classical chemotherapy in some settings. Cooperative effects of CDK4/6 inhibitors with other chemotherapeutic drugs, such as cisplatin or gemcitabine have been reported in bladder, lung, ovarian, and pancreatic cancer models (Gao et al, 2017;Gelbert et al, 2014;Kumarasamy et al, 2019;Rubio et al, 2019). In ovarian cancer, CDK6 phosphorylates FOXO3 and induces ATR to protect those cells from platinum-induced cell death, supporting the use of CDK4/6 inhibitors after cisplatin to treat these tumors (Dall'Acqua et al, 2017).…”
Section: Cdk4/6 Inhibitors and Immunotherapymentioning
confidence: 91%